DFT study of the enhancement on hydrogen production by alkaline catalyzed water gas shift reaction in supercritical water. (26th July 2018) - Wang, Runyu; Guo, Liejin; Jin, Hui; Lu, Libo; Yi, Lei; Zhang, Deming; Chen, Jia
Abstract: Supercritical water gasification (SCWG) is hopefully to be an acceptable choice for hydrogen production, the hydroxide ion assisted water gas shift reaction (WGSR) has been regarded as the most important reaction to generate hydrogen during the process. However, the principle of practical OH − catalyzed reaction is not possible to acquire by experiments. Thus, density functional theory (DFT) is utilized to investigate the reaction mechanism theoretically in this work. Through first principle calculations, every species and energy barrier for elementary steps are achieved, and formate ion is determined as the important intermediate. Besides, HCOO −  + H2 O → HCO3 −  + H2 is the dominant path to generate hydrogen, as well as the rate-determining step with 47.94 kcal/mol energy barrier. Furthermore, the reaction rate constant is calculated to be kcatalytic (s −1 ) = 2.34 × 10 12 exp(−1.80 × 10 5 /RT) using transition state theory with Wigner transmission coefficient (TST/w). Lastly, supercritical water condition is demonstrated to be a favored media for WGSR, because it may dissociate, dissolve or hydrolyze more hydroxide anion than conventional steam. The results are expected to benefit the control of reaction process and the design of SCWG reactor. Highlights: The mechanism of OH catalyzed water gas shift reaction was investigated. HCOO −  + H2 O → HCO3 −  + H2 was the rate-determining reaction. The reaction rate constant was calculated: k(s −1 ) = 2.34 × 10 12 exp(−1.80 × 10 5 /RT). The advantages of supercritical water was demonstrated.